A Comparative Study of the Pratimoksa, on the Basis of its Chinese, Tibetan, Sanskrit and Pali Versions. W. Pachow. - Heirman, Ann (Buddhist Studies Review, 2001)
A Comparative Study of the Pratimoksa, on the Basis of its Chinese, Tibetan, Sanskrit and Pali Versions. W. Pachow. (Buddhist Tradition Series 31), Motilal Banarsidass, Delhi 2000. 240 pp. Rs 395, €26.33. ISBN 81-208-1572-6.